Open trial of exposure therapy for PTSD among patients with severe and persistent mental illness. (March 2016) - Grubaugh, Anouk L.; Clapp, Joshua D.; Frueh, B. Christopher; Tuerk, Peter W.; Knapp, Rebecca G.; Egede, Leonard E.
Abstract: Objective: There are few empirical data regarding effective treatment of trauma-related symptoms among individuals with severe mental illness (SMI; e.g., bipolar disorder, schizophrenia). This under-examined clinical issue is significant because rates of trauma and PTSD are higher among individuals with SMI relative to the general population, and there are sufficient data to suggest that PTSD symptoms exacerbate the overall course and prognosis of SMI. Method: 34 veterans with SMI received prolonged exposure (PE) for PTSD using an open trial study design. Results: Data suggest that PE is feasible to implement, well-tolerated, and results in clinically significant decreases in PTSD severity in patients with SMI. Mean CAPS scores improved 27.2 points from baseline to immediate post [95% CI for mean change: −44.3, - 10.1; p = 0.002, paired t-test, and treatment gains were maintained at 6 months [mean change from baseline to 6-months, −16.1; 95% CI: −31.0, –1.2; p = 0.034, paired t-test]. Conclusions: The current data support the use of exposure-based interventions for PTSD among individuals with SMI and highlight the need for rigorous randomized efficacy trials investigating frontline PTSD interventions in this patient population. Highlights: There are few data on effective PTSD treatment practices for individuals with severe mental illness (SMI). Current study data support the use of exposure-based interventions for PTSD in individuals with SMI. Patients evidenced significant pre to post treatment decreases in PTSD severity. There were no adverse events and participants reported minimal distress with regard to their treatment participation.